Management of Persistent Pruritus and Lichenoid Reaction Secondary to Nivolumab With Narrowband Ultraviolet B Phototherapy - Donaldson, Marie; Owen, Joshua L.; Chae, Young K.; Choi, Jennifer N. (Frontiers in Oncology, 2018)
Immune checkpoint inhibitors targeting the programmed cell death receptor 1 (PD-1) are increasingly used to treat several malignancies, with the most common adverse event being cutaneous toxicity. We report the case of a 68-years-old man with stage IV non-small cell lung cancer treated with nivolumab who developed a pruritic, lichenoid eruption refractory to treatment with topical or systemic steroids, who was started on narrow band ultraviolet B therapy which resolved the reaction.